Tailoring atomic chemistry to refine reaction pathway for the most enhancement by magnetization in water oxidation - Wu, Tianze (2024)
Water oxidation on magnetic catalysts has generated significant interest due to the spin-polarization effect. Recent studies have revealed that the disappearance of magnetic domain wall upon magnetization is responsible for the observed oxygen evolution reaction (OER) enhancement. However, an atomic picture of the reaction pathway remains unclear, i.e., which reaction pathway benefits most from spin-polarization, the adsorbent evolution mechanism, the intermolecular mechanism (I2M), the lattice oxygen-mediated one, or more? Here, using three model catalysts with distinguished atomic chemistries of active sites, we are able to reveal the atomic-level mechanism. We found that spin-polarized OER mainly occurs at interconnected active sites, which favors direct coupling of neighboring ligand oxygens (I2M). Furthermore, our study reveals the crucial role of lattice oxygen participation in spin-polarized OER, significantly facilitating the coupling kinetics of neighboring oxygen radicals at active sites.